Learning on other people's kids : becoming a Teach for America teacher - Veltri, Barbara Torre (Emerald Publishing Limited : Information Age Publishing, 2010)
This work captures the voices of TFA novices who offer candid accounts of their experiences in Becoming Teach For America Teachers. Previously unanswered questions are addressed: Why do recent college graduates apply to Teach For America? How are they recruited, trained, and hired? How do they learn the culture (s) of the community, schools, grade level, curriculum, and children they teach? Is there a "culture" of the TFA organization? What recommendations do they offer to TFA donors, policy-makers, future corps members and the public?Woven into this book, are perspectives from mentors who worked alongside TFAers, administrators who hired them, corporate C.E.O.'s who supported them, and policies (both local and national) that privileged TFA over non-TFA teachers. Finally, a compelling series of eyewitness narratives introduces each chapter's theme, documented from the author's own, "Notes from the Field." These accounts offer rich, descriptive vignettes that present the challenges TFAers faced, as they occurred. Schools reflect the multitiered and often non-level playing field that comprises America's educational landscape. Learning on Other People's Kids: Becoming a Teach For America Teacher provides readers a glimpse into the corps member experience in a rare ethnographic account.